A study of synaptic connection between low threshold afferent fibres in common peroneal nerve and motoneurones in human tibialis anterior - Orawan Prasartwuth (2018)
We have induced H-reflex responses in human tibialis anterior motor units and analysed the results using the classical technique, peristimulus time histogram (PSTH), and a new technique, peristimulus frequencygram (PSF). The PSF has recently been shown to be more reliable than the PSTH for indicating the synaptic connections on motoneurones, and therefore we wished to examine the differences between the two analysis methods. Experiments were conducted on eleven healthy subjects (7 males and 4 females) who did not have any known neurological disorder. The subject sat comfortably on a dental chair and the common peroneal nerve was stimulated. In each experiment, about 600 electrical stimuli were applied to the nerve randomly between 1 and 2 s. The recordings were taken with both by surface electromyogram (SEMG) and as single motor unit potentials. We found that, when a stimulus induces an H-reflex, it also generates a period of reduced activity (silent period) and a long latency excitation in the PSTH. However, the PSF records in general do not match the indications of the PSTH records. For example, when the PSTH indicated existence of a silent period immediately following the H-reflex response, the discharge rate of the unit was in fact higher than the prestimulus rate. On the contrary, during the PSTH illustrated long latency excitatory response, the discharge rate was lower than the prestimulus rate. Our findings suggest that PSF gives significantly different results compared with the PSTH in determining the synaptic connection of the low threshold muscle afferents to the motoneurones. While PSTH indicated that there was a silent period immediately after the H-reflex, the PSF demonstrated that the silent period was actually a continuation of the net excitatory effect and not a genuine inhibition since the small number of action potentials occured during this period displayed higher discharge rates than the prestimulus level. Furthermore, the long latency excitation, as it was indicated in the PSTH; was actually a net inhibitory effect since the large number of spikes that occured during that period had lower discharge rates than the prestimulus average. In the lights of the recent brain slice findings and completely different results obtained using the two analysis techniques, we suggest that the PSF analysis should be used along with the PSTH to illustrate the net synaptic connection between peripheral receptors and motoneurones in the human nervous system. © 2008 Springer-Verlag.